Continuous glucose monitoring for hypoglycemia and diabetic ketoacidosis risk reduction among diabetic patient using insulin: A literature review - Rohmah, Assyfa Siti; Herawati, Tuti (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Hypoglycemia and diabetic ketoacidosis (DKA) are the two most common complications in diabetes patients. Monitoring blood glucose levels to prevent acute complications is an important part of diabetes management. In the era of increasingly advanced technology, technology can be used to monitor blood glucose, namely continuous glucose monitoring (CGM).Purpose: To provide an overview of the effectiveness of using CGM devices as diabetes management to reduce the incidence of hypoglycemia and DKA in diabetes patients receiving insulin therapy.Method: Literature review research to identify through a database all articles related to the topic of the effectiveness of continuous glucose monitoring (CGM). Literature search using boolean search with population